2015
DOI: 10.1111/jifm.12043
|View full text |Cite
|
Sign up to set email alerts
|

IFRS and Secrecy: Assessing Accounting Value Relevance Across Africa

Abstract: We examine the value relevance of accounting across several African countries and test whether IFRS improved the value association of earnings and equity book values. We report a stronger valuation association between accounting and stock prices in African countries classified as having a secrecy culture. This increases after IFRS and more so for earnings. On the other hand, IFRS induced a stronger increase in the book value coefficient in the less secretive and more developed South African market. We surmise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 91 publications
0
16
0
1
Order By: Relevance
“…Whereas there are contradictory findings on the impact of IFRS on attracting capital (Nnadi and Soobaroyen, 2015; Hessayri and Saihi, 2018), there is a general assertion that IFRS has value relevance in Africa (Hiller et al , 2016; Outa et al (2017). We also identify that some of the generalised findings from prior research on consequences are of limited significance in the African context.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Whereas there are contradictory findings on the impact of IFRS on attracting capital (Nnadi and Soobaroyen, 2015; Hessayri and Saihi, 2018), there is a general assertion that IFRS has value relevance in Africa (Hiller et al , 2016; Outa et al (2017). We also identify that some of the generalised findings from prior research on consequences are of limited significance in the African context.…”
Section: Introductionmentioning
confidence: 65%
“…On the impact of IFRS on reporting in Africa, Outa et al (2017) found that revised and converged IFRS gives relevance to value; however, the value relevance in East Africa is relatively lower compared to the developed market. Similarly, in five African countries, Hiller et al (2016) reported value relevance for book and earnings coefficients after IFRS adoption, indicating a strong valuation association between earnings and equity book value. Additionally, they found that in a “secret” culture like Africa’s, the relationship is much stronger and hence, training of accountants to harness the benefit of IFRS is needed.…”
Section: Ifrs Consequencesmentioning
confidence: 91%
“…Thus, we include MB to control for the impact of unconditional conservatism. Aubert and Grudnitski (), Hillier, Hodgson, and Ngole (), and Jermakowicz, Prather‐Kinsey, and Wulf () argue that accounting standards, particularly IFRS adoption, influence the managerial behavior of financial reporting. We use USGAAP or IFRS, an indicator variable that equals 1 if a firm adopts U.S. Generally Accepted Accounting Principles ( USGAAP ) or International Financial Reporting Standards ( IFRS ) and 0 otherwise, to control for accounting standards.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, managing inflation expectations is very important because it is the core aspect of monetary policy. According to Hillier et al (2016), secretive cultures prevent users from seeing the upward movements of inflation in financial statements because it is easy to conceal earnings and asset values. Businesses engage in these concealments to avoid the responsibility of accounting to external investors.…”
Section: Empirical Review On the Consideration Of Inflation In Organimentioning
confidence: 99%